Síntese de betalaínas induzida pela luz em espécies do gênero Alternanthera - Reis, Andressa (2013)
A characteristic of plants and other sessile organisms is their ability to synthesize a wide variety of low molecular weight compounds, called secondary metabolites. Among these compounds are the betalains, hydrophilic molecules of two types: red-violet betalains and yellow betaxanthins. These phytochemicals have been widely used because of their high antioxidant activity and free radicals scavenging. The light intensity and quality are important factors in plant growth and development and specific changes in light quality severely affect physiological, morphological and biochemical plant parameters. Thus, the aim of the present study was to evaluate the effect of light quality on growth and accumulation of secondary metabolites from callus and plant species of the genus Alternanthera, as well as a protocol establishment for callus induction of these plants. The species A. brasiliana, A. philoxeroides and A. sessilis had their explants placed on MS medium with different combinations of growth regulators. In the experiment of callus induction only plants of A. brasiliana were used, which were maintained for 45 days of culture under white light and in the second experiment, with the induction protocol already established, were used the three species of Alternanthera and the callus maintained in culture for 40 days under different light qualities (blue , white and red). The analysis to quantify betacyanin in HPLC-MS on experiment in A. brasiliana callus confirmed that they have expressive content of amaranthin and on calluses of different species experiment, the best response was observed in A. brasiliana plants and the internodes were considered the best explants. Studies of callus in different light qualities demonstrated that blue light induces the production of glycosylated betacyanin and betaxanthins. Thus, it is concluded that the quality of light significantly affects the biosynthesis of betacyanin, betaxanthins and flavonoids, as well as the growth patterns of Altemanthera plants.